Tourism Education in Azerbaijan: Current Situation, Problems and Solutions - Teymur Sarkhanov, Gadir Bayramli, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Tourism has been chosen as one of the priority areas among non-oil sectors. Although there are prerequisites for the development of tourism in a country with rich natural and historical-cultural recreation resources, the use of the country's rich tourism potential is not sufficient. One of the reasons why tourism cannot achieve any result is the problems of tourism education. This problem is also delaying the transition to the sustainable development of tourism. These reasons make it necessary to carry out research on tourism education, identify and solve problems. Some issues related to tourism education have been touched upon in the Strategic Roadmap for Tourism Development, tourism-related programs, and some tourism textbooks, and highlighted the importance of solving the problem. Almost all tourism education institutions and most of the qualified cadres in tourism are concentrated in the capital Baku and other major cities. This indicates that there is an inequality in the location of skilled cadres in the field of tourism, and according to these figures, the regions are far behind the major cities like Baku, Ganja, and Sumgait. Investigation of tourism education requires comprehensive and systematic analysis. Statistical analysis, comparative analysis, and SWOT analysis methods have been used in this article, which examines the problems of tourism education in Azerbaijan. If problems on tourism education are solved, it will be possible to make better use of the country's recreational potential and improve the quality of tourism services. The problem of tourism education is to increase the number of enterprises providing tourist education, to study and apply the experience of developed countries, to strengthen the staff in the tourism education institutions, to introduce innovative methods of teaching, to improve the quality of textbooks, to enhance tourism education in the regions, and to provide internship opportunities for students and young researchers to meet their needs.